STRATEGI PENGELOLAAN OBYEK WISATA TAMAN MARGASATWA SEMARANG - Wendi Efri Saputro; Aufarol Marom; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2014)
Semarang City is one tourist destination in Central Java Province, which has the potential to invite many tourists to visit. One of the attractions of interest to tourists  visited Semarang is Wildlife Areas (TMS). Wildlife Areas Semarang is one place in the city of Semarang tourism and wildlife conservation that combines the concept of education (learning about animals and life). The function  and role of the park's wildlife is in the field of education, namely as a means of science and technology education. As well as a place for family entertainment that educates various groups. However, in the management of Wildlife Areas are still not optimal, it is shown by the low interest of tourists to visit the Wildlife Areas Semarang. The purpose of the study to describe the condition of the internal and external conditions faced by Wildlife Areas Semarang, and analyze the strategies that should be prioritized in tourism management Wildlife Areas Semarang. The results showed that the management of a tourist attraction Wildlife Areas Semarang not optimal. The cause of non-optimal management can be seen from the internal and external factors of  wildlife Semarang areas covering of the lack of means of infrastructures, the quality of human resources, lack of budget and lack of tourism awareness groups. It is recommended to do for tourism management strategies Wildlife Areas Semarang, such as : Supervision of Culture and Tourism Semarang more comprehensive, attractive existence promo for visitors, Conducting coaching and persuasive approach to the community about the environment in order to grow  the attitude attraction of tourism awareness and Improving the quality and quantity of human resources.